Answer:
Ian is 194 cm tall now
Explanation:
Let the height of Jim be x
Now we are given that Ian is 14 cm taller than jim.
So,height of Ian be x+14
Now we are given that Lisa is 10 cm taller than her friend ian.
So, height of Lisa be x+14+10=x+24
Since their heights increase by 2 cm every months
So after 7 months ,
Jim's height =
![x+(7 *2)=x+14](https://img.qammunity.org/2019/formulas/mathematics/high-school/zz2d41yjnwi7s03le5x27eqf44lg2dg402.png)
Ian's height=
![x+14+(7 *2)=x+28](https://img.qammunity.org/2019/formulas/mathematics/high-school/cx5jnowjmow60e838ary23caitv79qc6b3.png)
Lisa's height=
![x+24+(7 *2)=x+38](https://img.qammunity.org/2019/formulas/mathematics/high-school/qo5s5t0gvpqebhsumphuhqj31h5y48lamt.png)
Now we are given that In 7 months, the sum of ian's and jim's height will be 170 cm more than lisa's height.
So,
![x+14+x+28=x+38+170](https://img.qammunity.org/2019/formulas/mathematics/high-school/fyvfz7n9bhy5x2q9k28rmial5ojel9ib16.png)
![x+42=208](https://img.qammunity.org/2019/formulas/mathematics/high-school/gtg0llp4k5je305vyhr76g4b190s4pobz0.png)
![x=208-42](https://img.qammunity.org/2019/formulas/mathematics/high-school/jtm9j5ux8lljfhyv4piiwp4k024ilc0w0m.png)
![x=166](https://img.qammunity.org/2019/formulas/mathematics/high-school/659ur06lcy518ozlsu66olw9bed3xpq98x.png)
So, Ian's height = x+28 =166+28 = 194 cm
Hence Ian is 194 cm tall now